1999
DOI: 10.1111/j.1469-7793.1999.0327t.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C activators induce membrane retrieval of type II Na+‐phosphate cotransporters expressed in Xenopus oocytes

Abstract: The homeostasis of inorganic phosphate (Pé) in mammals is primarily determined by the rate of Pé reabsorption at the brush border membrane in the renal proximal tubule. This process is mediated by an electrogenic Na¤-coupled cotransport system involving a specific cotransporter protein which has been designated the type II Na¤-Pé cotransporter (reviewed in . Pé reabsorption via this system can be modulated directly at the functional protein level by pH, extracellular ionic composition and membrane potential (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 41 publications
(93 reference statements)
8
41
1
Order By: Relevance
“…7, none of these mutations had an effect on the PTH response. In agreement with this observation, removal of all protein kinase C sites on the rat IIa was unable to prevent the protein kinase C-dependent effect when tested in the Xenopus laevis oocytes system (48,49).…”
Section: K503r504 Residues Aresupporting
confidence: 65%
“…7, none of these mutations had an effect on the PTH response. In agreement with this observation, removal of all protein kinase C sites on the rat IIa was unable to prevent the protein kinase C-dependent effect when tested in the Xenopus laevis oocytes system (48,49).…”
Section: K503r504 Residues Aresupporting
confidence: 65%
“…The PMA effect in oocytes could not be mimicked by the inactive phorbol ester 4␣-PDD. However, only partial suppression of DOG inhibition was produced by staurosporine, in both oocytes and HEK293 cells, corresponding to previous findings for NaPi-II (30). This might be partly attributable to the opposing (i.e., inhibitory) effect observed with staurosporine alone.…”
Section: Discussionsupporting
confidence: 53%
“…This investigation was designed to determine whether transport inhibition occurs at the cell membrane or is achieved via carrier internalization and whether any of the classic PKC consensus sites of hOAT1 are involved. As our main expression system, we used X. laevis oocytes, which have been used for a variety of studies on the regulation of carriers and ion channels, such as the sodium/dicarboxylate cotransporter NaDC-1 (32), the sodium/phosphate cotransporter NaPi-II (30,34), the sodium/ glucose cotransporter SGLT1 (35), and the epithelial Na ϩ channel ENaC (36). In some cases, this system reflects regulation in the original cellular environment more accurately than does the HEK293 cell system (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study we have shown that, in oocytes, transport activity correlates with the transporter present in the surface membrane but not with the total amount of protein (23). Here, we have measured Na ϩ -dependent P i uptake and its pH dependence for all the different constructs.…”
Section: Resultsmentioning
confidence: 99%